Oxidative stress mediated platelet activation in patients with congenital analbuminemia: Effect of albumin infusion. (16th October 2021) - Baratta, Francesco; Bartimoccia, Simona; Carnevale, Roberto; Stefanini, Lucia; Angelico, Francesco; Del Ben, Maria
Abstract: Background and Aims: Congenital analbuminemia is a rare autosomal recessive inherited disorder characterized by strongly decreased concentration, or complete absence, of serum albumin (SA). Several lines of evidence indicate that SA has anti‐thrombotic effect. In vivo platelet function and the role of oxidative stress (OS) in platelet aggregation promotion have never been studied in analbuminaemic patients. Patients and Methods: We report two cases of congenital analbuminemia in a 38‐year‐old male and in a 67‐year‐old woman. We analyzed platelet activation (PA) and OS at baseline and 2 h after 40 g human albumin infusion. PA was evaluated as platelet aggregation, sCD40L and surface αIIbβ3 integrin and P‐selectin expression. OS was evaluated measuring serum sNOX2dp, and 8‐iso‐PGF2α. Findings: Analbuminemic patients displayed higher platelet aggregation, markers of PA and of OS. Albumin infusion reduced platelet activation by reducing oxidative stress.